2015
DOI: 10.3389/fpls.2015.00917
|View full text |Cite
|
Sign up to set email alerts
|

Validation of molecular markers associated with boron tolerance, powdery mildew resistance and salinity tolerance in field peas

Abstract: Field pea (Pisum sativum L.) is an important grain legume consumed both as human food and animal feed. However, productivity in low rainfall regions can be significantly reduced by inferior soils containing high levels of boron and/or salinity. Furthermore, powdery mildew (PM) (Erysiphe pisi) disease also causes significant yield loss in warmer regions. Breeding for tolerance to these abiotic and biotic stresses are major aims for pea breeding programs and the application of molecular markers for these traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…More recently, Sudheesh et al [16] identified a major QTL for B tolerance in field pea and developed a putative marker for the region that was associated with both powdery mildew (PM) resistance and B tolerance. While validating this marker across a selection of germplasm and breeding lines, Javid et al [3] confirmed a strong link between B tolerance and PM resistance (r = 0.959) but the marker incorrectly predicted B tolerance in 21% of cases. Concordant with screening results reported by Javid et al [3], we found Kaspa and Sturt to be sensitive to B.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, Sudheesh et al [16] identified a major QTL for B tolerance in field pea and developed a putative marker for the region that was associated with both powdery mildew (PM) resistance and B tolerance. While validating this marker across a selection of germplasm and breeding lines, Javid et al [3] confirmed a strong link between B tolerance and PM resistance (r = 0.959) but the marker incorrectly predicted B tolerance in 21% of cases. Concordant with screening results reported by Javid et al [3], we found Kaspa and Sturt to be sensitive to B.…”
Section: Discussionmentioning
confidence: 99%
“…While validating this marker across a selection of germplasm and breeding lines, Javid et al [3] confirmed a strong link between B tolerance and PM resistance (r = 0.959) but the marker incorrectly predicted B tolerance in 21% of cases. Concordant with screening results reported by Javid et al [3], we found Kaspa and Sturt to be sensitive to B. However in that study, Sturt presented the B tolerant marker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SSR primer synthesis and PCR amplifications were performed as described above. SNP genotyping was performed using KASP™ genotyping chemistry (LGC, Middlesex, UK) as described in Javid et al (2015). …”
Section: Methodsmentioning
confidence: 99%